The IBJI central bank and ministry of finance year book 1987/88 - Rae, Richard (London : New Times (in association with IBJ International), 1987)
The year book contains the most up-to-date and accurate information source relating to the two key financial authorities of every country worldwide.
Includes index.
ne 29/09/2021
Ref.
Keywords: Banks and banking, Central; Government financial institutions